Wood waste as a fuel for timber drying - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In developing countries considerable quantities of sawdust and other particulate residues are generated by local industries. These residues, a potential source of energy, are often discarded as a waste product. Engineers at the Natural Resources...